Implementasi Metode Penemuan Terbimbing Terhadap Kemampuan Representasi Matematika Ditinjau Dari Keaktifan Belajar Siswa - Ariesta, Ovie Tiya; , Rita P. Khotimah, S.Si., M.Sc (2015)
The background of this research was the undeveloped of student's mathematical representation ability. Therefore it is necessary to encourage the application of learning that is able to explore the capabilities of student, ie learning by guided discovery method. The purpose of this study was to determine: (1) the effect of guided discovery method to the mathematical representation ability (2) the effect of student's learning activeness to the mathematical representation ability (3) The interaction between guided discovery method based on student's learning activeness to the mathematical representation ability. This research is a quasi experimental research design posttest-only control group. The population in this study is all of the 9th grade student of 3rd Colomadu Junior High School academic year 2014/2015. The sample's research consisted of two classes totaling 61 student. The sampling technique used cluster sampling. Data collection techniques through tests, questionnaires, and documentation. Data were analyzed using two-way analysis of variance with different cells. The results obtained from the analysis of data with a significance level α = 5%, are: (1) There is no effect the implementation of guided discovery method to the mathematical representations ability with FA = 1,329 (2) There is an effect among student's learning activeness to the mathematical representations ability with FB = 8,665 (3) There is no interaction between the method of guided discovery based on student's learning activeness to the mathematical representation ability with FAB = 0,883